Educational competences in the virtual modality teachers, students, and the world of work - Wall Lumseyfai, Jennifer (2021)
This article aims to reflect on the development of skills in the virtual modality in the 21st century through the study of teachers, students, and the workforce after formal education is complete. This essay seeks to interpret which of the competencies are necessary for teachers to teach effectively including the competencies necessary for teaching, the prior information teachers need for effective teaching and planning, the competences for teaching learning as well as the value and evaluation of teaching and learning. Secondly, this essay investigates the competencies of the students in the virtual world including pedagogical competence (learning to learn), communication, psychological competence (socio-emotional learning), digital competence and investigative competence. Finally, the essay connects the capacities of both teachers and students to view the competencies that are essential for today’s workforce. These skills include leadership, group work, education, and digital learning. Together these three focuses allow for a clear path from those who are teaching how to learn, those who are learning, and those who are applying their learning in a virtual setting.